PENURUNAN TINGKAT STRES IBU HAMIL DENGAN TERAPI MUSIK DAN AROMATHERAPY PADA KELAS IBU HAMIL - Ananti Setya Primawati; Melyana Nurul Widyawati; Admini Admini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
Preeclampsia is one of the causes of the high maternal mortality rate (MMR) in Indonesia. In Banyumas District, preeclampsia is the highest cause of MMR in January-June 2018 period. One of the risk factors of preeclampsia is the stress level in pregnancy. Prolonged levels of stress can lead to psychological changes in increased levels of adrenal and cortisol hormones. Non-pharmacological treatment techniques that can be used are music therapy and aromatherapy.The purpose of this study was to determine the effect of the addition of music and aromatherapy therapy on pregnancy class on the stress level of pregnant women.This research is a miniriset with the type of pre-experimental research using one group pretest posttest design. A sample of 20 pregnant women who attended pregnancy class. Measurement of stress levels was carried out before and after the intervention using the Perseived Stress Scale (PSS).The mean level stress before the intervention 18.60 with minimum value 12 and maximum value 27. Meanwhile, the mean level stress after intervention 18.30 with minimum value 11 and maximum value 27. There was decrease in stress levels 0.30. Based on the results of the study, it is expected that the increase in pregnancy class is accompanied by the addition of non-pharmacological therapies to overcome psychological problems in pregnant women such as music therapy and aromatherapy.